Damage tolerance of carbon-carbon composites in aerospace application. (January 2018) - Chowdhury, Piyas; Sehitoglu, Huseyin; Rateick, Richard
Abstract: We investigate fatigue-cracking behavior of unidirectionally reinforced carbon-carbon composites with different fiber orientations aimed for aerospace applications. Through digital image correlation (DIC), full field displacements are recorded in-situ, which capture the evolution of strain localizations during cyclic loading. DIC displacement fields are further utilized to determine crack driving forces via a regression analysis of orthotropic constitutive relations. Microscopic computerized tomography (micro-CT) scans disclose the competing nature of damage micromechanism e.g. pore coalescence, fiber bridging etc. for an advancing crack. Electron microscopy of fractured surfaces reveals widespread fiber/matrix interface debonding and fiber pullout, which chiefly contribute to cyclic cracking resistance. Upon sufficient progression, cyclic crack growth is observed to be self-arresting in nature unless applied loads are further increased. The origin of such behavior is attributed to: (a) reduction of driving forces due to continually degrading composite elastic modulus and (b) enhanced damage impedance originating from resistive tractions due to pervasive fiber bridging and pullout in the wake. Graphical abstract: Image